The role of Toll-like receptors in skin diseases - Bacharewicz, Joanna; Reduta, Teresa; Flisiak, Iwona (Dermatology Review/Przegląd Dermatologiczny, 2014)
The innate immune system has the ability to recognize pathogens through Toll-like receptors (TLRs), which are transmembrane glycoproteins on the cell surface. These receptors present on the surface of immunological cells – macrophages, dendritic cells, mast cells and some populations of lymphocytes – play an important role in the defense against bacterial, viral and fungal infections. The connection of a Toll-like receptor with the microbial cell component known as pathogen associated molecular pattern (PAMP) induces intracellular mechanisms leading to the synthesis of proinflammatory cytokines. Depending on the kind of the recognized ligand, TLRs are classified into subfamilies. So far, 13 TLRs have been described in mice and 11 in humans. These receptors may be expressed extracellularly (TLRs 1, 2, 4, 5, 6, 10, 11) or intracellularly, located in endosomes (TLRs 3, 7, 8, 9). Recent studies also indicate their role in the development of many dermatoses. Occurrence of these receptors has been found on the surface of epidermal and dermal cells: keratinocytes, Langerhans cells, fibroblasts, endo-thelial cells, melanocytes and adipocytes. This paper presents the structure and function of Toll-like receptors and their role in the pathogenesis of some infectious skin diseases, autoimmune and allergic dermatoses as well as skin neoplasms. The knowledge about the role of Toll-like receptors in the development of skin diseases creates the possibility to use them in treatment in the future.